Examining second language receptive knowledge of collocation and factors that affect learning. (May 2017) - Nguyen, Thi My Hang; Webb, Stuart
This study investigated Vietnamese EFL learners' knowledge of verb–noun and adjective–noun collocations at the first three 1, 000 word frequency levels, and the extent to which five factors (node word frequency, collocation frequency, mutual information score, congruency, and part of speech) predicted receptive knowledge of collocation. Knowledge of single-word items at the same word frequency levels was also examined. The results indicated that the participants were not close to a level of mastery of collocational knowledge at any word frequency level; knew less than 50% of each type of collocation overall; and that their knowledge of collocation significantly decreased at each level. The analysis also revealed that there were significant large positive correlations between knowledge of collocations and single-word items, and that node word frequency was the strongest predictor of receptive knowledge of collocation.